Involvement of microRNA-146a in diabetic peripheral neuropathy through the regulation of inflammation - Feng Y; Chen L; Luo Q; Wu M; Chen Y; Shi X (Dove Medical Press, 2018)
Yonghao Feng,1 Long Chen,2 Qiong Luo,2 Men Wu,1 Yinghui Chen,2 Xiaohong Shi1 1Department of Endocrinology, Jinshan Hospital, Fudan University, Shanghai, China; 2Department of Neurology, Jinshan Hospital, Fudan University, Shanghai, China Purpose: Recent evidence has shown the involvement of inflammation in the development of diabetic peripheral neuropathy (DPN). MicroRNA-146a (miR-146a) is closely involved in the inflammatory response. However, the role of miR-146a in the inflammatory reaction in DPN has not been clarified. This study was designed to explore the role of miR-146a in the regulation of inflammatory responses in DPN.Methods: Rats were randomly divided into three groups (n=6 per group): control group, type 2 diabetes mellitus (T2DM) group and DPN group. T2DM and DPN rats were intraperitoneally injected with streptozotocin. Sciatic nerve conduction velocity (NCV) was determined at the 6th week and the 12th week in each group. The expression of microRNAs was detected by quantitative real-time polymerase chain reaction in three sciatic nerves for each group of rats. Expression of inflammatory cytokines in nerve tissues and plasma was measured by Western blot and Bio-Plex Pro™ assays.Results: The NCV and expression levels of miR-146a in the DPN group were significantly decreased (P<0.01) compared to the other two groups. Expression of tumor necrosis factor alpha (TNF-α), interleukin 1 beta (IL-1β) and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) in the DPN group was significantly increased compared with the control and T2DM groups (P<0.01). Pearson’s correlation analysis showed that the expression level of miR-146a was negatively correlated with the levels of IL-1β, TNF-α and NF-κB.Conclusion: miR-146a is involved in the pathogenesis of DPN, and its expression level is closely related to the inflammatory responses that aggravate sciatic nerve injuries. Keywords: type 2 diabetes mellitus, diabetic peripheral neuropathy, microRNA-146a, NF-κB, cytokines